Allelopathic action of parthenium and its rhizospheric soil on maize as influenced by growing conditions - Safdar,M.E. (2014)
Biosynthesis and subsequent release of allelochemicals by a plant into the environment is supposed to be influenced by its growing conditions. To ascertain what will be the allelopathic action of plant parts and rhizospheric soils of parthenium (Parthenium hysterophorus) growing at various farm locations with varied growing conditions, germination and seedling growth of maize hybrid (DK 6142) were assayed by sowing its seeds in petri plates lined with filter paper and pots filled with soil. Minimum germination percentage (30.0%), germination index (2.01), germination energy (36.3), seedling length (3.3 cm), seedling biomass (10 mg) and seedling vigor index (99.0) of maize were observed in leaf extract followed by fruit and whole plant extracts of parthenium growing near the field border. Rhizospheric soil collected underneath parthenium growing near a water channel caused maximum reductions in germination index (30.8%), germination energy (40.6%), seedling length (32.6%), seedling biomass (35.1%) and seedling vigor index (34.3%) of maize compared with that soil without any vegetation. Phytotoxic inhibitory effects of both parthenium plant and rhizospheric soil were more pronounced on maize root than its shoot growth. The higher suppressive action against germination and seedling growth of maize was probably due to higher total phenolic concentrations (6678.2 and 2549.0 mg L-1) and presence of phenolic compounds viz., gallic, caffeic, 4-hydroxy-3-methoxy benzoic, p-coumaric and m-coumaric acids; and ferulic, vanillic, syringic and m-coumaric acids in aqueous leaf extract of parthenium uprooted near the field border and its rhizospheric soil collected near a water channel, respectively.